Point-of-care C-reactive protein testing to reduce inappropriate use of antibiotics for non-severe acute respiratory infections in Vietnamese primary health care: a randomised controlled trial - Do, NTT; Ta, NTD; Tran, NTH; Than, HM; Vu, BTN; Hoang, LB; van Doorn, HR; Vu, DTV; Cals, JWL; Chandna, A; Lubell, Y; Nadjm, B; et al. (Elsevier, 2016)
Background Inappropriate antibiotic use for acute respiratory tract infections is common in primary health care, but distinguishing serious from self-limiting infections is difficult, particularly in low-resource settings. We assessed whether C-reactive protein point-of-care testing can safely reduce antibiotic use in patients with non-severe acute respiratory tract infections in Vietnam.